Focusing on Mouth Movement to Improve Genuine Smile Recognition - Ruan, Qian-Nan; Liang, Jing; Hong, Jin-Yu; Yan, Wen-Jing (Frontiers in Psychology, 2020)
Smiles are the most commonly and frequently used facial expressions by human beings. Some scholars claimed that the low accuracy in recognizing spontaneous smiles is explained by perceptual-attentional hypothesis, meaning they are either didn’t pay attention to responsible cues or unable to recognize these cues (usually on Duchenne marker or AU6 displaying as contraction of muscles in eye regions). We investigated whether training (instructing to either pay attention to Duchenne mark or dynamic lips) might help improve the recognition of spontaneous smiles, including accuracy and confidence. Results showed that attention to dynamic lips improves one’s ability to distinguish between spontaneous and posed smiles, with nullification of the alternative explanations such as sample distribution and intensity of lip pulling (AU12). This study further argues that the perceptual-attentional hypothesis can explain smile spontaneity recognition.